Synthesis and Characterization of N-Substitutional Ethylenediamine Derivatives - Yao, Ri-sheng; Jiang, Lai-en; Wu, Sheng-Hua; Deng, Sheng-song; Yang, Yang (Asian Journal of Chemistry, 2011)
N-Substituted and N,N-disubstituted ethylenediamine derivatives were prepared rapidly in aqueous conditions from 30 to 76 % yields, respectively, on a multi-gram scale starting from inexpensive and commercially available starting materials. The steps involved Michael addition, hydrazinolysis and Curtius rearrangements. The highlight of this method lies on its convenience and economy in accessing these intermediates.